EPS instructors' perceptions of factors that affect students' oral performance - Dogruer, Nazan; Menevis, Ipek; Eyyam, Ramadan (Elsevier Science Bv, 2010)
The aim of this study is to find out the perceptions of instructors about the factors that affect the speaking performance of students during the exam. This study took place in Eastern Mediterranean University (EMU). The participants were the full-time instructors at the English Preparatory School (EPS) during the 2008-2009 Academic Year Spring Semester. A questionnaire was prepared and was given to full-time EPS instructors. The collected data was analyzed. As a result, it was found out that the instructors believed that students' familiarity to the task types and some of attitudinal differences of them could affect their exam results. (C) 2010 Elsevier Ltd. All rights reserved.
2nd World Conference on Educational Sciences (WCES-2010) -- FEB 04-08, 2010 -- Bahceschir Univ, Istanbul, TURKEY
Keywords: EPS instructors' perceptions; students' oral performance; speaking performance; English Preparatory School; EPS instructors